PENGARUH APLIKASI MIKORIZA TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA PEMBIBITAN MAIN NURSERY - Githa Noviana; Mariani Sembiring; Mardiana Wahyuni; Guntoro (Program Studi Agroteknologi INSTIPER, 2018)
Nursery is the beginning of the process to reach optimum production, so proper treatment is necessary. To reduce side effects on the environment and higher fertilizing costs, we employ mycorrhyza that is expected to increase efficiency and effectiveness of the production process. The purpose of this research is to understand the effects of mycorrhyza application on the vegetative growth of palm oil at the main nursery. This research is using non-factorial Randomized Completely Block Design with 4 (four) treatments and six repetitions that used 24 samples by observing the growth of the tree trunk, its diameter, and number of leaves. The last observation was conducted to know the degree of mycorrhyza infection in every treatment. The results showed that mycorrhyza application had no significant effect on the growth of the plant and trunk diameter, but it has very significant effect on the growth of the leaves at the last week. The more significant result was observed at M3 with 75 gram dosage. The infection degree at the end of the research showed a very significant effect with average value of 6.00 at M3 compared to M1 with 4.00 value. Keywords: mycorrhyzae, oil palm, main mursery